Implementasi Manajemen Wi-Fi Terpusat Menggunakan OpenWISP pada Gedung Multi-Lantai: Evaluasi Seamless Roaming dengan SSID Tunggal dan Quality of Service (QoS) - Lutfi Abdilah; Desi Rahmayanti (Institut Agama Islam Negeri (IAIN) Curup, 2026)
Wi-Fi management in multi-floor buildings often faces challenges such as uneven signal coverage, the emergence of dead zones, and roaming failures when users move between floors. Prior studies have largely relied on commercial controllers, while empirical evidence on the implementation and measurable evaluation of open-source solutions in multi-story building scenarios remains limited. This study implements OpenWISP as a centralized Wi-Fi management platform with a single-SSID configuration to support seamless roaming, and applies Quality of Service (QoS) to maintain service stability and fair bandwidth allocation. The evaluation was conducted through QoS testing across multiple floors using Speedtest CLI, measuring latency, jitter, throughput, and packet loss, complemented by observations of signal coverage before and after access point repositioning. The results show idle latency below 10 ms across all floors, download throughput of 7.91–9.42 Mbps and upload throughput of 1.72–2.33 Mbps, with packet loss ranging from 0% to 0.9%. During inter-floor mobility, packet loss was recorded at 0%, indicating that roaming operated seamlessly. These findings demonstrate that OpenWISP is effective in improving service quality, reducing mobility-related disruptions, and simplifying centralized access point management in multi-floor buildings.